2022
DOI: 10.5354/0719-0581.2022.60808
|View full text |Cite
|
Sign up to set email alerts
|

Inmigración en La Araucanía, ¿cómo viven este proceso haitianos, colombianos y venezolanos?

Abstract: El proceso migratorio y la adaptación a la cultura receptora presentan una serie de desafíos únicos para los inmigrantes, los cuales repercuten en su nivel de ajuste psicosocial. Este estudio busca caracterizar a tres grupos de inmigrantes. Usando un muestreo intencionado de tipo bola de nieve se encuestó a 150 inmigrantes, provenientes de Colombia (n = 50), Venezuela (n = 50) y Haití (n = 50). Todos eran mayores de edad y residían en la región de La Araucanía. Los participantes contestaron escalas de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Scientific evidence has corroborated that this process presents various difficulties that extend from the pre-migration phase and the migration journey itself to the arrival and settlement in the host country [ 29 ]. Research has linked migration processes to symptoms of stress, anxiety, depression, psychosomatic symptoms (e.g., headaches and stomach problems) and mental health disorders in general [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence has corroborated that this process presents various difficulties that extend from the pre-migration phase and the migration journey itself to the arrival and settlement in the host country [ 29 ]. Research has linked migration processes to symptoms of stress, anxiety, depression, psychosomatic symptoms (e.g., headaches and stomach problems) and mental health disorders in general [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this crisis in the northern macrozone, immigrants have had to look for settlement alternatives in the south of Chile [ 7 , 11 , 12 ]. This increase in migratory flows to new places of settlement in southern Chile highlights the need to understand how these acculturation processes affect the migrant population depending on the characteristics of the place of settlement, especially if these new settlements present particularities, such as intergroup conflicts and social vulnerability [ 13 ], considering that, in addition, Chile has stratified access to the health system and is one of the most unequal countries in the world [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that migrants informed higher levels of nostalgia for their home country alongside experiences of discrimination, adaptation difficulties, and problems with their migratory regulation process, which implies several issues in obtaining access to health care, jobs, and housing, among others. Moreover, Chilean people struggle with the same concerns, which converts the migration to Chile into a highly challenging settlement [ 13 , 26 , 27 ]. Accordingly, this study hypothesises that, in immigrants, acculturative stress is positively related to mental health symptoms (H1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation